(untitled) (المجلة الدولية للعلوم التربوية والآداب, 2025)
This study aimed to evaluate the relationship between the roles of digital media and its ability to enhance awareness of cybersecurity threats in the banking sector in the Kingdom of Bahrain. This study employed a descriptive method and relied on a questionnaire as a data collection tool from a sample of the study. The researcher formulated a questionnaire consisting of 20 items in addition to the demographic data of the participants. The study sample comprised 400 participants from the banking sector in the Kingdom of Bahrain, which was divided into an exploratory sample of 35 participants and a main sample of 365 participants. This sample was collected intentionally. Through statistical analysis, the study reached a set of results, the most important of which is that employees in the banking sector in the Kingdom of Bahrain have a high level of awareness of cybersecurity threats that could disrupt the services provided by banks and represent a danger to the confidentiality of customer data and their banking transactions. Digital media, through its various means, plays important roles in raising awareness among banking sector employees to enhance cybersecurity. One of the most prominent roles is to enhance the awareness of workers in the banking sector about the importance of protecting personal information and customers’ banking data. There is a statistically significant relationship between the digital media used in banks and the level of awareness among employees about countering cyber-attacks. There are no statistically significant differences in the opinions of banking sector employees regarding the role of digital media in enhancing awareness of cybersecurity threats attributed to variables (gender - age - position - type of bank). It has been recommended to employ digital media more effectively to simplify the digital content published about cybersecurity and make it more engaging and interesting. It has also been suggested that there should be interaction with the digital content published about the cyber threats faced by banks and inquiring with specialists about the nature of threats that are difficult to understand.